PENGARUH IMPLEMENTASI ECLECTIC METHOD TERHADAP PRESTASI BELAJAR SISWA PADA PEMBELAJARAN BAHASA ARAB - Salbiah (Al-mujahidah, 2020)
There are frequent complaints of some students regarding the difficulties in learning Arabic both in listening skill (مَهَارَةُ الْإِسْتِمَاعِ), speaking skill (مَهَارَةُ الْكَلَامِ), reading skill (مَهَارَةُ الْقِرَاءَاةِ), and writing skill (مَهَارَةُ الْكِتَابَةِ). This research is aimed at testing the مت Eclectic Method (طَرِيْقَةُ الْاِنْتِقَائِيَةِ) for students' Arabic learning. The results of the completion of the pre-test and post-test one group design above indicate that t_count> t_table with a significant level of 5% or 0.05, namely 8.46> 2.064. based on the result, the researcher concludes that Ho is rejected and Ha is accepted. Therefore, there is a significant influence between the implementation of the Eclectic method on students' Arabic learning.